Non-Verbal Cues in Physician-Patient Communication (International Journal of Innovative Research in Engineering & Management, 2022)
Communication in the health sector is dominated by non-verbal elements, which are an essential  variable in doctor-patient relations. Besides helping to  develop relationships, nonverbal communication gives  clues about unseen fears and emotions, as well as  confirming or contradicting spoken statements. Albeit  less natural to comprehend, nonverbal correspondence  continues in calm and can take numerous structures on  the double, capacities on a less cognizant level, and  communicates unconstrained signs. It is likewise the  channel generally liable for communicating perspectives,  sentiments and influence. Patients' and physicians' non verbal communication is closely connected. Nonverbal  signals in speech patterns, facial expressions, and body  posture must be recognized and investigated by  physicians. Not only this, but patients must also be  conscious of their own non-verbal behaviour. A  developing collection of exploration has connected  physician’s nonverbal correspondence, (for example, eye  contact, head gestures and signals, and voice position and  tone) to the accompanying results: patient fulfilment,  patient agreement, doctor discovery of passionate misery,  and doctor misbehaviour guarantee history, in the course  of the most recent 20 years. Thus, the present paper  intends to identify the different types of non-verbal  elements that appear to be dominant in physician-patient  communication.
Keywords: Non-verbal Cues; Physician; Patient; Communication